2017
DOI: 10.9738/intsurg-d-17-00098.1
|View full text |Cite
|
Sign up to set email alerts
|

The Type of Anesthesia Technique Does Not Have an Impact on 30-Day Mortality in Geriatric Patients Undergoing Lower Extremity Amputation

Abstract: This study aimed to determine the appropriate anesthetic technique for patients who underwent amputation due to peripheral vascular disease. The anesthetic technique to be applied during lower extremity amputations in geriatric patients with limited functional capacity may be important in terms of clinical outcomes and mortality rates. Patients aged older than 65 years who had undergone major lower extremity amputation were retrospectively evaluated. The patients were divided into 2 groups: regional anesthesia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…[ 11 12 ] Out of the 10 studies, two did not control for confounders. [ 13 14 ] The rest of the studies utilised either multivariate logistic regression[ 12 15 16 17 ] or propensity score matching[ 4 11 18 19 ] to adjust for confounders. With the exception of one study which was reported by SA Khan et al ,[ 4 ] all of the eight studies that controlled for confounders reported no significant benefit of RA over GA in reducing the incidence of 30-day mortality after LEA [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…[ 11 12 ] Out of the 10 studies, two did not control for confounders. [ 13 14 ] The rest of the studies utilised either multivariate logistic regression[ 12 15 16 17 ] or propensity score matching[ 4 11 18 19 ] to adjust for confounders. With the exception of one study which was reported by SA Khan et al ,[ 4 ] all of the eight studies that controlled for confounders reported no significant benefit of RA over GA in reducing the incidence of 30-day mortality after LEA [ Table 2 ].…”
Section: Resultsmentioning
confidence: 99%
“…Six studies[ 4 12 13 14 15 17 ] reported the length of hospital stay (H-LOS). There is some evidence that H-LOS is shorter in patients who received RA compared to GA. Three studies[ 13 14 15 ] reported a statistically significant shorter H-LOS with the use of RA with mean differences ranging between 3.7 to 5 days. [ 13 15 ]…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations